O patrimônio urbano-arquitetônico de Caxias do Sul (RS): resgate memorial das edificações para possível utilização turística - Bisol, Letícia Eloisa (My University, 2018)
Presenting one of the constituent elements of the tourist attraction, buildings of historical and memorial values, safeguarded by the public administration, within the urban context, this master’s dissertation aims to evolutionarily analyze the municipality of Caxias do Sul (Brazil), as well its official historical landmark collection for possible tourist use. It is a transdisciplinary study, with relations between urban architectural heritage, city, tourism, culture, memory, and identity. For this dissertation, it was used a qualitative exploratory research, with the following methodological procedures: bibliographic, documental, iconographic and ethnographic research. It is intended to understand the city’s development in relation to the urban, architectural, and legal evolution; how has the current city’s master plan begun, and the involved social actors; how has the local preservation/conservation process made; the preserved materials’ survey; the relations between the City Master Plan, the buildings listed as historical heritage and Tourism; and verify if those legally-protected landmarks are in the memory of their residents, using interviews found in the collection of the Municipal Historical Archive. The municipality of Caxias do Sul is addressed as an empirical object, distinguishing it as a specific category of analysis when it is intertwined with distinct areas in the search of an urban tourism potential, respecting the law, but also bringing back memory and identity to its community.
A presente dissertação apresenta um dos elementos constituídos do atrativo turístico, ou seja, edificações de valor histórico e memorial salvaguardadas pelo poder público local, inseridas no contexto urbano. Com o presente trabalho tem por objetivo analisar município de Caxias do Sul (RS) evolutivamente, bem como seu acervo tombado para possível utilização turística. Trata-se de um estudo transdisciplinar que faz relações envolvendo o patrimônio urbano-arquitetônico, a cidade, o turismo, a cultura, a memória e identidade. A metodologia teve orientação qualitativa exploratória e com os seguintes procedimentos metodológicos: pesquisa bibliográfica, documental, iconográfica e etnográfica. Procura-se compreender o desenvolvimento da localidade com a evolução urbana, arquitetônica e também de sua legislação; como se deu o processo para o surgimento do Plano Diretor Municipal atual, e seus atores sociais envolvidos; como se deu o processo de preservação/conservação local; o levantamento dos bens materiais preservados; as relações entre o Plano Diretor Municipal, as edificações tombadas e o Turismo; e se este patrimônio protegido por meio legal encontra-se na memória de seus moradores, utilizando entrevistas encontradas no acervo do Arquivo Histórico Municipal. Elenca-se o município como objeto empírico, diferenciando-o como categoria específica de análise ao entrelaçar distintas áreas, na busca de um potencial turístico urbano, respeitando a legislação, mas também devolvendo à comunidade sua memória e identidade.
Keywords: Turismo cultural - Caxias do Sul (RS); Arquitetura; Turismo - Caxias do Sul (RS); Heritage tourism - Caxias do Sul (Brazil); architecture; Tourism - Caxias do Sul (Brazil)